Extraction of caffeine from PBC123 - Nur Farahin, Mohd Razlan (2012)
Caffeine is one of the few plant products with which the general public is readily familiar because of its occurrence in beverages such as coffee and tea,as well as various soft drinks.Its chemical formula is C8H10N4O. Moreover,caffeine can naturally be found in cocoa seeds such as Prang Besar Cocoa (PBC) 123.PBC 123 one of cocoa clone that can be found in Malaysian Cocoa Board plantaion at Jengka, Pahang. Commonly,the alkaloid contents (caffeine,theobromine,and theophylline) in cocoa are extracted before the cocoa is processed and the caffeine are discarded without use whereas the caffeine has its own benefits.For example,it is used for pharmaceutical purposes and the caffeine has increasing demand in the world.Moreover,an effective and low cost solvent is also needed for better extraction of caffeine. This will increase the profit from the sales of caffeine. Thus,this research will find the best solvent for the high extraction yield and also will optimize the parameters that affect the extraction yield of caffeine. The purpose of this research is to extract caffeine from Prang Besar Cocoa (PBC) 123.Besides that, this research is also to investigate the effect of sample particle size,extraction time and solvent/feed ratio on the yield of caffeine.Firstly,the seeds dried at 60˚C for 1hour.Then,the dried seeds will blend and sieved into 5 different particles size which is 2000,1000,800,630 and 315 µm.5g of powdered seeds will boiled with 250mL distilled water in batch heat reflux extractor for 15,30,45,60 and 90 minutes.For liquid-liquid extraction, solvent extraction will done using ethyl acetate at solvent or feed ratio of 1:5, 1:4, 1:3, 1:2 and 1:1. The lower layer that contains caffeine will collect.Rotary evaporator will used to evaporate ethyl acetate at 78˚C. Finally,the yields of caffeine in the solution will analyze by using UV/Vis Spectrophotometric method. The caffeine yield was highest at sample particle size of 315μm (0.27% w/w caffeine or 2.739 mg/g cocoa), solvent/ feed ratio of 1:1 (0.26% w/w caffeine or 2.614 mg/g cocoa), and extraction time of 90 minutes (0.26% w/w caffeine or 2.637 mg/g cocoa). The best conditions for the highest yield of caffeine from PBC123 were 315μm of sample particle size, 1:1 of solvent/feed ratio and 90 minutes of extraction time.